The Relationship Between Body Weight and Stress and Nutritional Status in Turkish Women - Sanlier, N.; Unusan, N. (Pakistan Journal of Nutrition, 2007)
The aim of this study was to examine the effects of body weight on stress and nutrition in women. Data were gathered from 889 women living in Turkey. The participants were selected randomly. Women were informed that the purpose of the study was to gather information on stress and nutrition and each participant attended a face-to-face interview. Subjects were administered a questionnaire containing demographic profile, anthropometric measurements, daily energy and macro-nutrients intakes, Stress Scale were used for descriptive purposes. Stress Symptom Scale, Stress Related Factors, Susceptibility to Stress Scale and Total Score were significantly associated with Body Mass Index (BMI) and daily energy and nutrients intake. Underweight and obese women had higher stress scores than normal weight women (p